Recursos e habitats para conservação do guigó (Callicebus coimbrai) em Sergipe - Baião, Sirley Almeida Adelino (2017)
Coimbra-Filho’s titi monkey, Callicebus coimbrai, is an endemic primate of the Atlantic Forest of the Brazilian Northeast, found only in Sergipe and northern Bahia. The species has been the focus of research and conservation efforts over the past twelve years, which has integrated the region’s scientists and institutions. The study presented here provides continuity, with three distinct, but complementary approaches. The first approach was an ecological study in the Mata do Junco Wildlife Refuge, in the municipality of Capela, in the Brazilian state of Sergipe. The results of this study highlighted the ecological resilience of the species in the face of habitat fragmentation. The titi is relatively inactive, spending most of the day at rest, and is predominantly frugivorous, although the proportion of time spent foraging was higher than in most previous studies of the same group, which may be related to variation in observational procedures. While some significant variation was found in the composition of the diet, the behavior of the members of the study group changed very little between the different periods of the year, or even among years, in comparison with previous years. Two aspects of the behavior of the animals were highlighted, however. One was the breakdown in the dispersal mechanism from the natal group, which apparently resulted in an endogamous mating between the resident reproductive male and its mature daughter. This is the second case of endogamy recorded in C. coimbrai, which may result from the inflexible social organization of the species in the context of habitat fragmentation, and represents a potentially serious problem for the long-term conservation of the species. The second new behavior was the predation of termites (Nasutitermes sp.), which appears to reflect the behavioral flexibility of C. combrai, and may represent a positive feature of the capacity of the species to cope with habitat fragmentation. In the second theme, the ecological concept of keystone species/resources was reviewed through a systematic literature search, which aimed to evaluate the potential practical applications of the concept for the conservation of C. combrai. This review revealed an extensive literature, which has grown almost exponentially in recent years, although the concept has been applied relatively rarely in primate studies. Together with the data accumulated on the ecology of the species, the discussion of the concept indicated that the extension of forest is a keystone resource for the conservation of C. coimbrai. This conclusion supports the third approach, which was an evaluation of the potential for the implementation of a network of ecological corridors in the study area. The analysis identified three priorities for the formation of corridors, one in the buffer zone of the RVS Mata do Junco, the second to the south of the area, and the third linking the refuge to the AIE Mata do Cipó. The thesis provides valuable insights into the long-term conservation of the species, but emphasizes the need for integrated efforts in research and practical action by environmental organs, research institutions, and the local population.